Risk Factors for 28-day Mortality Among COVID-19 Patients in an Intensive Care Unit of a Tertiary Care Center in Istanbul - (:unkn) unknown (GALENOS YAYINCILIK, 2021)
Objective: In late 2019, the Coronavirus disease 2019 (COVID-19) has been pandemic worldwide, starting in Wuhan, China. In this study, we aimed to evaluate the factors associated with 28-day outcomes in patients admitted to the intensive care unit with the diagnosis of COVID-19. Method: This study has a retrospective cohort design. COVID-19 patients identified according to World Health Organization guidelines are included. Patient data were recorded to a centralized system utilizing ImdSoft-Meta vision/QlinICU Clinical Decision Support Software. Individual datasets about required parameters were obtained from Structured Query Language (SQL) queries. The main laboratory parameters were examined. SOFA, APACHE II, and Charlson Comorbidity Score (CCS) were calculated. In evaluating laboratory parameters and disease risk scores, which are thought to affect 28-day mortality, logistic analysis were performed using the Backward LR model. Results: The study was carried out with 101 patients, 40 (39.6%) of whom were women, and 61 (60.4%) of men, who met the inclusion criteria. The ages of the patients ranged from 21 to 88, and the mean age was 58.45 +/- 15.41 years. The mean intensive care hospitalization period was 12.5 +/- 10.2 days. The all-cause in-hospital mortality rate was 61.4%. Leukocyte count, CK, NT-proBNP, PCT, CRP, ferritin, neutrophil count and percentage, D-Dimer, LDH, AST values were found to be significantly higher in non-survivors. The lymphocyte count and percentage, and platelet count values were found to be significantly low in non-survivors. The lymphocyte percentage, LDH, and CCS were significant in the 28-day mortality in multivariate analysis (p values are 0.01, 0.003, 0.008, respectively). Conclusion: High lymphocyte values have been found to significantly reduce the risk of death in patients diagnosed with COVID-19. Lymphocyte percentage, LDH, and CCS were evaluated as the most successful parameters in predicting 28-day mortality in the intensive care unit.
Keywords: COVID-19; Charlson Comorbidity Score; Mortality; Risk factors; SARS-CoV-2; CLINICAL CHARACTERISTICS; WUHAN; CHINA